Peoples Participation in the Physical Planning Activities: A Case Study of Khulna Development Authority - Ahmed, Sabrina; Swapan, Mohammad Shahklul Hasan (Journal of Bangladesh Institute of Planners, 2012)
In contemporary world, community participation is considered as the prerequisite of sustainable urban development. It ranges from just informing people about the plan or development projects by the people. However, public participation in local government’s led programs is still limited in Bangladesh. Considering the importance of community participation, this paper explores the level of public participation in spatial planning practices in Khulna city based on the citizen’s responses. The study suggests that existing legislative arrangement is not supportive for participatory urban development at all levels and a little provision is made in this respect by laws. Most of the respondents in the field survey suggested that political problem and weak communication mechanism are mainly responsible for unsuccessful implementation of the Master Plan of Khulna city. The study may help related authorities to understand the citizen’s expectations in designing strategies for performing better role in city development in Bangladesh. DOI: http://dx.doi.org/10.3329/jbip.v2i0.9567 Journal of Bangladesh Institute of Planners Vol. 2, December 2009, pp. 61-70